2003
DOI: 10.1089/104303403322542301
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Type 5: Transduction Efficiency and Cell-Type Specificity in the Primate Retina

Abstract: Gene transfer using adeno-associated viruses (AAVs) has been effective for treating inherited retinal diseases in animal models. Further evaluation in primates must be performed prior to clinical application, however, because of the difference between the retina of the primate and those of other animals. Prior work has shown that AAV2 can transduce rod-photoreceptor and RPE cells in the non-human primate retina and that AAV5 is more efficient at transducing photoreceptor cells than AAV2 in the rodent retina. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 26 publications
0
66
0
1
Order By: Relevance
“…31,32 For example, transduction of both RPE and photoreceptor cells can be achieved by subretinal injection of either AAV2 or AAV5; however, the efficiency of transduction appears much greater with AAV5, especially in photoreceptors. 33,34 The aim of this project was to evaluate various human cone opsin promoters for their specificity and efficacy to target gene expression to the canine cone photoreceptors. We were able to successfully target gene expression to the canine L/M cones using the human red cone opsin promoter PR2.1 in rAAV5.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 For example, transduction of both RPE and photoreceptor cells can be achieved by subretinal injection of either AAV2 or AAV5; however, the efficiency of transduction appears much greater with AAV5, especially in photoreceptors. 33,34 The aim of this project was to evaluate various human cone opsin promoters for their specificity and efficacy to target gene expression to the canine cone photoreceptors. We were able to successfully target gene expression to the canine L/M cones using the human red cone opsin promoter PR2.1 in rAAV5.…”
Section: Discussionmentioning
confidence: 99%
“…19 A recent study has shown that in primates, rAAV-5/5 also has preferential tropism for rod photoreceptors. 29 For chimeric vectors rAAV-2/5 and rAAV-2/4, subretinal injection in dogs results in stable expression of GFP for more than 18 months (Rolling et al, data not shown), with the tropism being identical to the one observed in the rat: transduction of RPE and photoreceptor cells with type 5 and exclusive transduction of RPE with type 4. 26 …”
Section: Gene Transfer In Large Animalsmentioning
confidence: 99%
“…There may also be promoter-serotype interactions. AAV5, for example, does not transduce macaque primate cones effectively with the CMV promoter (Lotery et al 2003), but it is effective in cones of the squirrel monkey when using a cone-specific promoter (Mancuso et al 2007). It is impossible to precisely predict whether AAV2 will limit photoreceptor gene expression exclusively to rod photoreceptors in any given human retinal degeneration; however, it is probably safe to say that AAV2 will target rods more effectively than cones in humans.…”
Section: Choosing a Gene Therapy Vectormentioning
confidence: 99%